2021
DOI: 10.3389/fonc.2021.752725
|View full text |Cite
|
Sign up to set email alerts
|

Improving Outcomes of Tyrosine Kinase Inhibitors in Hepatocellular Carcinoma: New Data and Ongoing Trials

Abstract: Targeted therapies such as oral tyrosine kinase inhibitors (TKIs) are the main therapeutic strategy effective for advanced hepatocellular carcinoma (HCC). Currently six tyrosine kinase inhibitors for HCC therapy have been approved. The newly approved first-line drug donafenib represent the major milestones in HCC therapeutics in recent years. However, drug resistance in HCC remains challenging due to random mutations in target receptors as well as downstream pathways. TKIs-based combinatorial therapies with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…Mutations or overexpression of TKRs are frequently detected in cancer cells ( 61 , 62 ), leading to oncogenic transformation and tumoral progression. Therefore, the implementation of MKIs drugs in clinical practice determined important clinical implications in many human cancers such as leukaemia ( 63 ), renal carcinoma ( 64 , 65 ) and hepatocellular carcinoma ( 66 , 67 ). Alike, MKIs had extensive applications in thyroid oncology, both in the treatment of radioactive iodine-refractory differentiated thyroid carcinoma ( 68 , 69 ) and in advanced medullary carcinoma ( 57 , 70 ).…”
Section: Multikinase Inhibitorsmentioning
confidence: 99%
“…Mutations or overexpression of TKRs are frequently detected in cancer cells ( 61 , 62 ), leading to oncogenic transformation and tumoral progression. Therefore, the implementation of MKIs drugs in clinical practice determined important clinical implications in many human cancers such as leukaemia ( 63 ), renal carcinoma ( 64 , 65 ) and hepatocellular carcinoma ( 66 , 67 ). Alike, MKIs had extensive applications in thyroid oncology, both in the treatment of radioactive iodine-refractory differentiated thyroid carcinoma ( 68 , 69 ) and in advanced medullary carcinoma ( 57 , 70 ).…”
Section: Multikinase Inhibitorsmentioning
confidence: 99%
“…It was found that 5–10% of lung cancer patients develop resistance to TKIs due to c-MET gene amplification [ 54 ]. This amplification, leading to ErbB3-dependent PI3K activation, contributes to tumor resistance to gefitinib [ 55 ]. HGF can induce resistance to gefitinib in lung adenocarcinoma patients with EGFR mutations by phosphorylating c-MET and activating the PI3K/Akt signaling pathway through an ErbB3-independent pathway [ 56 ].…”
Section: The Signaling Pathways In Tumor Drug Resistancementioning
confidence: 99%
“…A combination of immune checkpoint inhibitors and tyrosine kinase inhibitors could be a breakthrough treatment modality, but defects in interferon-γ or insufficient tumor antigen immunosuppressive cells in the tumor microenvironment develop resistance to immune checkpoint inhibitors [ 25 , 26 ]. Sorafenib and other TKIs have been used globally, and molecular biomarkers and genome changes in pathobiological issues have been emphasized [ 27 ]. However, varying outcomes in different metastatic locations have been studied.…”
Section: Discussionmentioning
confidence: 99%